Beneficial usage of social marketing for small and medium-sized enterprise (SME) in Johor / Hairiani Abdul Hamid ... [et al.] - Abdul Hamid, Hairiani; Kamarolzaman, Noraishah; Omar, Zurina; Wan Abdul Hamid, Wan Nazihah Najwa (UiTM Cawangan Johor, 2020)
The study that was carried out by the researchers is to find out the beneficial usage of social marketing for small-and medium-sized enterprises (SMEs) in Johor. A total of 100 sets of questionnaires have been distributed to the respondents at Nusajaya Johor. The respondents who were given the questionnaires were chosen using convenience sampling in order to get the data. It is a convenience kind of sampling which has been chosen by the researcher (repetition) The questionnaires are the primary data regarding the antecedents of social media usage and performance that benefit small-and medium-sized enterprises (SMEs). The independent variables obtained from the past research and modified for this research are interactivity, cost effectiveness and compatibility. The dependent variable which can be obviously seen is the performance benefits using social media for the private company. The data collected were then analysed by the researchers to get the final result that supports and answers the research objective. A few tests conducted in order to get the final result which can support the most suitable variable. The researchers found that only Interactivity strategy influencing the performance benefit of using social marketing as it is acceptable, the cost effectiveness is still in a questionable state which still can be accepted, and compatibility is unacceptable since it is less than 0.3.